Fasting and postprandial liver glycogen content in patients with type 1 diabetes mellitus after successful pancreas–kidney transplantation with systemic venous insulin delivery. (11th May 2013) - Stadler, M.; Krššák, M.; Jankovic, D.; Göbl, C.; Winhofer, Y.; Pacini, G.; Bischof, M.; Haidinger, M.; Saemann, M.; Mühlbacher, F.; Korbonits, M.; Baumgartner‐Parzer, S. M.; et al.
Abstract Background In patients with type 1 diabetes mellitus (T1DM), insulin is usually replaced systemically (subcutaneously) and not via the physiological portal route. According to previous studies, the liver's capacity to store glycogen is reduced in T1DM patients, but it remains unclear whether this is due to hyperglycaemia, or whether the route of insulin supply could contribute to this phenomenon. T1DM patients after successful pancreas–kidney transplantation with systemic venous drainage (T1DM‐PKT) represent a suitable human model to further investigate this question, because they are normoglycaemic, but their liver receives insulin from the pancreas transplant via the systemic route. Materials and methods In nine T1DM‐PKT, nine controls without diabetes (CON) and seven patients with T1DM (T1DM), liver glycogen content was measured at fasting and after two standardized meals employing 13C‐nuclear‐magnetic‐resonance‐spectroscopy. Circulating glucose and glucoregulatory hormones were measured repeatedly throughout the study day. Results The mean and fasting concentrations of peripheral plasma glucose, insulin, glucagon and C‐peptide were comparable between T1DM‐PKT and CON, whereas T1DM were hyperglycaemic and hyperinsulinaemic (P < 0·05 vs T1DM‐PKT and CON). Total liver glycogen content at fasting and after breakfast did not differ in the three groups. After lunch, T1DM‐PKT and T1DM had a 14% and 21% lower total liver glycogen content than CON (P < 0·02). Conclusion In spite of normalized glycaemic control, postprandial liver glycogen content was reduced in T1DM‐PKT with systemic venous drainage. Thus, not even optimized systemic insulin substitution is able to resolve the defect in postprandial liver glycogen storage seen in T1DM patients.